Exploring problematic experiences : an IPA study of 'Internet Addiction' - Allie, Naaheeda (Rhodes University, Faculty of Humanities, Department of Psychology, 2015)
In the past two decades, a considerable amount of research has been carried out on the phenomenon of excessive Internet use, variously termed Internet addiction, Internet dependency and problematic Internet use. Despite this, there is still little agreement as to what constitutes this phenomenon, whether it should be considered a clinical disorder or not and what leads to this excessive or maladaptive use. The terminology used in this study is that of Problematic Internet Use (PIU). Several theoretical models have been proposed in the understanding of PIU including personality models, operant conditioning models, social cognitive and cognitive behavioural models (Davis, 2001; LaRose, lin & Eastin, 2003; Young, 1999). A proposed gap in the literature is the lack of studies exploring participant experiences of problematic Internet use. It is for this reason that this study aimed at exploring the experiences of a small sample of individuals with self-identified problematic Internet use. The implications of this phenomenological data for the above-mentioned theoretical models were then reviewed. This study used an Interpretative Phenomenological Analysis (IPA) approach in exploring these aims. A sample of four participants was selected through purposive sampling techniques. Four major themes emerged from the analysis namely: Escapism, Social Insecurity and Validation, Perfectionism and Control. These experiences of participants were also explored in terms of the conceptual models reviewed in order to compare how closely they related to participant experiences. A strong inter-relationship was found between the four themes mentioned above. The Internet appeared to provide a sense of control and validation to these individuals while simultaneously rendering them unable to maintain control of their Internet usage in relation to this. This sense of control was experienced through an escape from negative emotions, offline obligations and at times a dissatisfactory position in reality. Of the four models reviewed, the Social Cognitive model proposed by LaRose et al. (2003) appeared to offer the most relevant understanding of PIU to participant experiences. The presence of maladaptive cognitions also appeared to feature strongly as an underlying factor in participants' PIU, as theorised by cognitive behavioural models (Davis, 2001; Young, 1999) Finally recommendations are made for further more detailed exploration of PIU using interpretative, experiential methods.
Keywords: Internet addiction; Compulsive behavior; Security (Psychology)